2020
DOI: 10.34117/bjdv6n8-586
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Da Adubação Orgânica E Mineral No Cultivo De Batata-Doce Na Região Amazônica

Abstract: Avaliação da adubação orgânica e mineral no cultivo de batata-doce na região AmazônicaEvaluation of organic and mineral fertilization in sweet potato cultivation in the Amazon region

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The introduction of crops with short cycles, such as sweet potato (Ipomoea batatas (L.) Lam), in intercropping is an income option, as it demands low production costs and has a relatively short cycle of 90 to 150 days until harvest (Silva;Lopes;Magalhães, 2008, Aguirre et al, 2020, Coelho et al, 2022. Sweet potato cultivation stands out for its profitability due to its simplicity of cultivation and low operational cost of development (Oloniyo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of crops with short cycles, such as sweet potato (Ipomoea batatas (L.) Lam), in intercropping is an income option, as it demands low production costs and has a relatively short cycle of 90 to 150 days until harvest (Silva;Lopes;Magalhães, 2008, Aguirre et al, 2020, Coelho et al, 2022. Sweet potato cultivation stands out for its profitability due to its simplicity of cultivation and low operational cost of development (Oloniyo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to data of the 2006 and 2017 Agricultural Census, the number of rural properties that use synthetic or organic compounds in the region in which the present work was carried out (Serra de Ibiapaba, CE, Brazil) increased from 7,505 to 8,703. Regarding the application of soil fertilizers to sweet potato crops using organic or mineral sources, researches have confirmed that the availability of nutrients is indispensable for high yield indexes (AGUIRRE et al, 2020;HIRATA, 2014). Sweet potato, as other vegetables, has a relatively high demand for primary macronutrients.…”
Section: Introductionmentioning
confidence: 99%
“…It has potential for use in tuberous roots and shoots, in human and animal food. Tuberous roots are an important source of low glycemic index carbohydrates, vitamins and minerals for the human diet, especially magnesium, potassium, phosphorus, and calcium (Aguirre et al, 2020;Nunes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Aguirre et al (2020), it was found that the tuberous roots of cream-colored sweet potato had higher levels of calcium than the tuberous roots of other colors. In this same context, the purple-colored tuberous roots are rich in anthocyanins (Adebamowo et al, 2015), and with orange-colored flesh, they are rich in beta-carotene (Vizzoto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%